Innovations, distribution gaps and mirror images: The reflexes of Proto-Ryukyuan close vowels in a post-nasal position - Jarosz, Aleksandra (Yearbook of the Poznan Linguistic Meeting, 2018)
Starting with an assumption that in some environments, the post-nasal raising of the mid-vowels led to the merger of original mid- and close vowels, while in different environments changes to the original close vowels keeps the reflexes of mid- and close vowels apart, the paper analyzes and compares Ryukyuan vocabulary containing the pertinent sound sequences of *mi, *mu, *ni and *nu, contrasting it with the reflexes of *me, *mo, *ne and *no. By scrutinizing in detail as many different environments of the sound sequences in question as possible, the paper aims to discover some patterns in the behavior of these sequences, examining both shared innovations and shared retentions among the daughter languages, observing the differences in the PR distribution of post-nasal mid-and close vowels, and entertaining the implications these findings hold for the general knowledge of PR.